Effects of MicroRNA on Regulatory T Cells and Implications for Adoptive Cellular Therapy to Ameliorate Graft-versus-Host Disease - Hippen, Keli L.; Loschi, Michael; Nicholls, Jemma; MacDonald, Kelli P. A.; Blazar, Bruce R. (Frontiers in Immunology, 2018)
Regulatory T cells (Treg), are key mediators of the immune system. MicroRNAs (miRNAs) are a family of 22 nucleotide non-coding RNAs that are processed from longer precursors by the RNases Drosha and Dicer. MiRNA regulate protein expression post-transcriptionally through mRNA destabilization or translational silencing. A critical role for miRNA in Treg function was initially discovered when both Dicer and Drosha knockout mice were found to develop a fatal autoimmune disease phenotypically similar to Foxp3 knockout mice.